DESIGN OF MANGOSTEEN HARVESTER TO IMPROVE HARVESTING EFFICIENCY - Andaffa, Siti Nazwa Nurul; Ichniarsyah, Annisa Nur; Musyarofah, Neni (Universitas Trilogi, 2025)
Most mangosteen farmers carry out the harvesting process manually by picking the fruit with hands or using a simple mangosteen harvester. As a commodity whose demand continues to increase, improvements in mangosteen harvesting methods are needed to increase the production and quality of agricultural products. The purpose of this study was to identify the components of the mangosteen harvester, to design how the tool works, to describe the harvesting process with the designed tool, and to produce technical drawings of the design. The study uses a quantitative descriptive approach including the physical characteristics of mangosteen fruit, collection of farmer anthropometric data, analysis of workload handling, engineering analysis, and design of tool components. The results of the study on the design of the mangosteen harvester consist of fruit basket components, telescopic poles with a maximum length of 4 meters, a trap net, locking clamps, and fruit protective foam. The tool works with the pulling force from the operator. This tool is designed using AISI 316 stainless steel. Load analysis was carried out using mangosteen release force data with various raya types, which is 1 N. The components of the mangosteen harvester tool were analyzed using the FEA feature with von mises stress, displacement, and factor of safety analysis so that the components are guaranteed to be safe. The design results can later be used to design tools to increase theoretical harvesting capacity, reduce fruit damage during the harvesting process, and increase harvesting time.